Description of two new Dismorphiini (Lepidoptera: Pieridae) with reflections of endemism in the Sierra Nevada de Santa Marta, Colombia - Llorente-Bousquets, Jorge; Le Crom, Jean François (Revista Colombiana de Entomología, 2013)
We describe two new subspecies in two species of Dismorphia Hübner, 1816, from the Sierra Nevada de Santa Marta in Colombia. It also provides a list of about 40 endemics taxa of Pieridae and Nymphalidae supporting taxonomic differentiation (evolutive) and biogeographic center of the Sierra (Nevada) de Santa Marta. We also recorded a Dismorphia amphione bertha as new taxon from from Amazonas, Colombia.